1968
DOI: 10.1136/sti.44.1.35
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of the treponematoses. II. Endemic treponematoses of childhood.

Abstract: We have seen in Part I of the present study that information on venereal syphilis has been available for more than a hundred years and that some of the human ecological factors could be assessed in the rise and fall of this adult treponemal disease. In the endemic treponematoses of childhood-on the other hand-knowledge of human ecological factors influencing recrudescence and regression is limited and the morbidity reporting of early and late manifestations of yaws, pinta, and endemic non-venereal syphilis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…However, Guthe and Willcox (1971) have observed that early syphilis is becoming more usual in many parts of Africa including Nigeria. Osoba (1972b) showed this was so in southern Nigeria when he reported a treponemal sero-reactivity rate of 2-8 % among 15 399 hospital patients, whereas Guthe and Ids0e (1968) reported a yaws incidence of only 0-2%. In fact, syphilis may soon become a problem because a new generation of young people is maturing without the immunity against syphilis that earlier generations possessed following their previous infection with endemic treponematosis-that is, yaws in the south and bejel in the north of Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…However, Guthe and Willcox (1971) have observed that early syphilis is becoming more usual in many parts of Africa including Nigeria. Osoba (1972b) showed this was so in southern Nigeria when he reported a treponemal sero-reactivity rate of 2-8 % among 15 399 hospital patients, whereas Guthe and Ids0e (1968) reported a yaws incidence of only 0-2%. In fact, syphilis may soon become a problem because a new generation of young people is maturing without the immunity against syphilis that earlier generations possessed following their previous infection with endemic treponematosis-that is, yaws in the south and bejel in the north of Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of gonorrhoea is high in Nigeria (Osoba, 1972) and it is rising as in many other parts of the world (Guthe and Idsoe, 1968;Guthe, 1972;Willcox, 1972). In developed countries, where there are adequate facilities for medical care, the course of gonorrhoea tends to be mild and complications are few.…”
Section: Introductionmentioning
confidence: 99%
“…They were applied world-wide in the many mass campaigns organized for the World Health Organization through the mediation of Thorstein Guthe, against yaws, pinta, and endemic syphilis; over 47 millions have now been treated as -clinical or latent cases or as contacts, and these campaigns have led to a dramatic fall in prevalence (Guthe and Ids0e, 1968). The conversion of penicillin G to penicillanic acid by Sheehan and Henery-Logan (1957) and the synthesis of phenoxymethyl penicillin (penicillin V) were the first steps leading to the many newer synthetic peniciuins.…”
mentioning
confidence: 99%